On the design of equity-oriented pharmaceutical copayments - Paula González (SERIEs - Journal of the Spanish Economic Association, 2020)
In this paper, we propose a new approach to address the problem of designing pharmaceutical copayments. The rationale for positive copayments in our setting lies in the presence of budgetary constraints and, hence, in the need to raise funds in order to finance the costs of the treatments. We use results from the literature on axiomatic bargaining with claims to incorporate criteria of distributive justice into the design of copayments. We find that if the government constrains patient rights to what is medically feasible, equity-based copayments vary from a percentage of the cost of the treatment, to a flat rate per prescription. If the government also takes into account the burden of disease experienced by patients, then copayments based on equity lead to a relation between copayments and clinical status that diverges from those proposals based on efficiency arguments. In particular, we show that equity-based copayments might be increasing in the health gains that the treatments provide to the patients. The reason is that these copayments try to avoid a "double jeopardy" problem, by ensuring that those patients with a large burden of disease do not face also an important monetary cost.
Keywords: I18; 330; Pharmaceutical copayments; Budget; Health; Equity; Proportional solution; Equal-loss solution; Axiomatic bargaining Claims